The Basic Education of the Rural Population: issues and impasses that cross the schooling process of these subjects - Valdirene de Jesus Ferreira; Rita de Cássia de Souza (Universidade Federal do Norte do Tocantins, 2023)
This article deals with the basic schooling of the rural population and presents partial results of a research project carried out as part of a master's degree, the main objective of which was to learn about the process of school dropout among rural residents in the municipality of Viçosa-MG. Therefore, the objectives of this work were: to demonstrate how the basic education offered to these residents has changed over time; to discuss the transition process from the proposal of rural education to that of education in the countryside; to discuss the policy of school nucleation, which has increased the dropout rates of students in the countryside and to present some impasses that cross the basic schooling process of these subjects. We carried out a literature review and interviews with fourteen rural residents who had dropped out of elementary school. Based on the analysis of these materials, we concluded that despite the increase in the schooling of the Brazilian population in recent years, rural dwellers continue to have difficulties making progress in the school process, participating in educational processes that take into account the specificities of their daily lives, which could contribute to their learning and strengthen their links with the school environment, reducing dropout rates. In short, there are challenges to guaranteeing access and permanence to basic education for the rural population that persist today and demand greater public investment.